Utilization of bamboo (Bamvusa blumeana) shoot powder for bangus (Chanos chanos) fish nuggets production - Santillan, Michael II
Fish nuggets were produced from bangus (Chanos chanos) surini and rehydrated bamboo (Bambusa blumeana) shoot powder.